SOCIAL NETWORKS AS A MODERN FORM OF MASS MEDIA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Social networks as a modern form of mass media The article considers social networks as a modern form of mass media. It is reported that the role of social networks in the life ofadm is growing. Also, social networks are classified and each type is characterized. They discussedin detail the trends, peculiarities, and characteristics of the media industry. Separate characteristicsare given to social media created for business and social networks created to meet the informational requirements of society. In general, it is noted that social networks have become an integral partof the ongoing processes in society
Keywords: mass media, media sphere, social network, freedom of speech, information security, media, hybrid systems.